2018
DOI: 10.1021/acs.jpclett.8b02178
|View full text |Cite
|
Sign up to set email alerts
|

Invalidity of Band-Gap Engineering Concept for Bi3+ Heterovalent Doping in CsPbBr3 Halide Perovskite

Abstract: Heterovalent CsPbBr doping with Bi results in a significant red shift of the optical absorption of both single-crystal and powdered samples. The results of low-temperature (3.6 K) photoluminescence studies of perovskite single crystals indicate that the position of the excitonic luminescence peak remains unaffected by Bi doping that, in turn, infers that the band gap of Bi-doped perovskite is not changed as well. The position and state density distribution of the valence band and Fermi level of single-crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 24 publications
(43 reference statements)
7
69
0
2
Order By: Relevance
“…Figure (d) shows the UV–Vis absorption spectra of different perovskite films, from which it is known that the band gap of the perovskite films does not change substantially with the increase in the present doping concentration range except for the local significant change in absorption intensity. This phenomenon is consistent with a recent report that heterovalent doping of CsPbBr 3 by Bi 3+ causes no band gap change but only but a shift in the Fermi level . However, the reason remains unclear presently.…”
Section: Resultssupporting
confidence: 93%
“…Figure (d) shows the UV–Vis absorption spectra of different perovskite films, from which it is known that the band gap of the perovskite films does not change substantially with the increase in the present doping concentration range except for the local significant change in absorption intensity. This phenomenon is consistent with a recent report that heterovalent doping of CsPbBr 3 by Bi 3+ causes no band gap change but only but a shift in the Fermi level . However, the reason remains unclear presently.…”
Section: Resultssupporting
confidence: 93%
“…28 Miyasaka and co-workers have also demonstrated that the band gap of Bidoped CsPbBr3 SCs is comparable to their un-doped case; also, they found that Bi 3+ doping causes no changes in the valence band structure, but an increase in the Fermi level of 0.6 eV is observed. 29 Hence, the decrease in PL intensity suggests that Bi 3+ ions are incorporated into the CsPbBr3 host lattice and create the bulk/surface trap states. In sharp contrast, Yao and co-workers incorporated lanthanide Ce 3+ dopants into the CsPbBr3 NCs lattice and achieved a significant enhancement in PLQY of up to 89% through increasing the dopant concentration.…”
mentioning
confidence: 99%
“…Bismuth has been reported to be an extremely effective means for bandgap tuning (redshift to be specific). [116] In addition, at low concentration of doping, Bi 3þ dopants have been found to fill the trap states and improve ionic conductivity of the perovskite; at a higher concentration of doping, they act as nonradiative recombination centers, leading to a transition from bimolecular recombination in pristine MAPbX 3 perovskites to a dominant trap-assisted monomolecular recombination process. [117,118] Abdi-Jalebi et al reported doping of MAPbI 3 with monovalent cations (Na þ , Cu þ , and Ag þ ) having an ionic radius similar to that of bivalent lead cations.…”
Section: Inorganic Dopantsmentioning
confidence: 99%